A Mean-Variance Model of MNF Location Strategy - Hanink, Dean M. (Journal of International Business Studies, 1985)
The purpose of this paper is to show that a portfolio theoretic model which directly incorporates the effect of interdependence among national markets can be useful in the analysis of an MNF's explicit location decisions. A numerical mean-variance portfolio model is developed and applied to the case of geographical expansion of the MNF. While international diversification may not be considered a necessary and sufficient cause for FDI, its effect on firm earnings should not be ignored in the MNF's location decisions.